Canine Assisted Occupational Therapy for Children on the Autism Spectrum: A Pilot Randomised Control Trial. - Hill, Jessica; Ziviani, Jenny; Driscoll, Carlie; Teoh, Ai Lin; Chua, Jia Min; Cawdell-Smith, Judy (Journal of Autism & Developmental Disorders, 2020)
Children on the autism spectrum frequently display difficulties engaging with people and with functional tasks. A pilot, randomised control trial was completed to explore the impact of canine assisted occupational therapy on the on-task behaviours and goal attainment of autistic children when compared to occupational therapy sessions as usual. Twenty-two children between the ages of 4, and 6 years and 11 months, were randomly placed in either the treatment group (n-11) or waitlist control group (n = 11). Results showed that although there was a positive trend for on-task behaviour and goal attainment within the treatment group, results were not statistically significant. These results support the need for further research in the area of canine assisted occupational therapy for autistic children.